27+6(2*2-1)4*2-5
2*2=4
27+6(4-1)4*2-5
4-1=3
27+6(3)4*2-5
6*3=18
27+(18)4*2-5
18*4=72
27+(72)*2-5
72*2=144
27+(144)-5
27+144+171
171-5=166
So the answer is 166.
Answer:
= (3t+2)(3t-2)(3t-4)
Step-by-step explanation:
Given the expression 27t^3 - 36t^2 - 12t + 16
On factoring:
(27t^3 - 36t^2) - (12t + 16)
= 9t²(3t-4)-4(3t-4)
= (9t²-4)(3t-4)
factoring 9t²-4
9t²-4 = (3t)² - 2²
From different of two square, a²-b² = (a+b)(a-b)
Hence (3t)² - 2² = (3t+2)(3t-2)
= (9t²-4)(3t-4)
= (3t+2)(3t-2)(3t-4)
Hence the factored form of the expression is (3t+2)(3t-2)(3t-4)
Answer:80
Step-by-step explanation:
Answer:
$9.3 million
Step-by-step explanation:
Given that the company profit increases by 9% yearly from 2005.
Using the exponential growth formula;
A = P(1+r)^(t) .....1
Where;
A = final amount/value of profit
P = initial amount/value = $6.6 million
r = growth rate yearly = 9% = 0.09
t = time of growth in years = 2009 - 2005 = 4 years
Substituting the values;
A = 6.6(1+0.09)^(4)
A = 6.6(1.09)^(4)
A = 9.3164386 million
A = $9.3 million
The companies profit in the year 2009 to the nearest 10th of $1 million is $9.3 million
The answers -2 because your taking the bigger number from the smaller number so you have to go into negative numbers